2014
DOI: 10.1021/jp500441h
|View full text |Cite
|
Sign up to set email alerts
|

A Bismuth Vanadate–Cuprous Oxide Tandem Cell for Overall Solar Water Splitting

Abstract: Through examination of the optoelectronic and photoelectrochemical properties of BiVO 4 and Cu 2 O photoelectrodes, we evaluate the feasibility of a BiVO 4 / Cu 2 O photoanode/photocathode tandem cell for overall unassisted solar water splitting. Using state-of-the-art photoelectrodes we identify current-matching conditions by altering the photoanode active layer thickness. By further employing water oxidation and reduction catalysts (Co-Pi and RuO x , respectively) together with an operating point analysis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
182
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(193 citation statements)
references
References 39 publications
(90 reference statements)
6
182
1
Order By: Relevance
“…60 This flat band potential is close to the values typically reported for BVO. 9,34,56 The noMo/T devices (blue traces) have a significantly better photocurrent onset (0. show below that the overall, spectrally integrated internal quantum efficiency of these Mo/T electrodes for sulfite oxidation at the OER potential (IQE = Z t = J/J abs ) is 70 AE 5%, limited by hole transport, and that the difference between the EE and SE photocurrents is due primarily to absorption losses in the FTO-coated glass substrate in the SE geometry. Recently, Seabold et al reported very similar results to our own -including a total IQE as high as 90% and larger photocurrent under EE than SE illumination -using 100-300 nm thick Mo:BVO films with a nanoporous morphology comparable to our films but without [001] texture.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…60 This flat band potential is close to the values typically reported for BVO. 9,34,56 The noMo/T devices (blue traces) have a significantly better photocurrent onset (0. show below that the overall, spectrally integrated internal quantum efficiency of these Mo/T electrodes for sulfite oxidation at the OER potential (IQE = Z t = J/J abs ) is 70 AE 5%, limited by hole transport, and that the difference between the EE and SE photocurrents is due primarily to absorption losses in the FTO-coated glass substrate in the SE geometry. Recently, Seabold et al reported very similar results to our own -including a total IQE as high as 90% and larger photocurrent under EE than SE illumination -using 100-300 nm thick Mo:BVO films with a nanoporous morphology comparable to our films but without [001] texture.…”
Section: àmentioning
confidence: 99%
“…phosphate, CoO x , metal oxyhydroxides) 8,9,14,18,[20][21][22]25,30,37,39,[50][51][52][53][54][55][56] to promote water oxidation and enhance BVO stability. Comparatively little work has been done to understand and optimize the light absorption, charge transport, and charge transfer properties of BVO itself.…”
Section: Introductionmentioning
confidence: 99%
“…By forming an electrical connection between these two electrodes, their individual potentials for driving water splitting reactions can be simply combined. [9][10][11][12] In such a system, a plausible working potential for the photoanode and photocathode is about 0.6 V RHE , and both electrodes need to generate a sufficient photocurrent at this potential to achieve efficient water splitting.…”
mentioning
confidence: 99%
“…3 At the other end of the spectrum are oxide-based devices, which can be cheap but show poor efficiencies. 4 Further development of these preprototype systems is needed as a precursor to the required industrial level scale-up to enable solar fuels to have a real impact. In this perspective, we will attempt to evaluate where the field has progressed and where there is still a need for breakthroughs to produce a viable solar fuels industry.…”
Section: Introductionmentioning
confidence: 99%